Surgical Neutering of a Tom Cat during Clinical Camp - Brahmbhatt, Ankita; Patel, Sanjay; Suthar, Vishal (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Castration or neutering in male pet animals is generally not practiced unless there is any testicular pathology or as a contraceptive means (Howe et al., 2000; Howe, 2015; Monin et al., 2019). Kamdhenu University, Gandhinagar operates an ambulatory clinic at village Sanoda, Tehsil Dehgam, Dist Gandhinagar, Gujarat and also participates in animal health and infertility camps treating large (Kapadiya et al., 2019; Brahmbhatt et al., 2020) and small animals (Mahesh et al., 2016, Momin et al., 2019). The pet canines presented in clinical camps are very less and felines are rarely brought for any medication or interventions in such camps. In this document such a rare case of 2 years old tom cat presented and successfully operated for neutering at the ambulatory clinic in a village without referring to secondary or tertiary set up is reported and discussed.